Fatigue resistance of monolithic lithium disilicate occlusal veneers: a pilot study - Baldissara, Paolo; Monaco, Carlo; Onofri, Enrico; Fonseca, Renata Garcia [UNESP]; Ciocca, Leonardo (My University, 2019)
The use of thin lithium disilicate (LD) occlusal veneers is an effective method to increase the vertical dimension of occlusion in cases of tooth wear. However, doubt remains regarding the threshold thickness to be used in this restoration class. This study aims to evaluate the effect of ceramic thickness on the survival rate and failure pattern of LD molar veneer restorations using a simplified fatigue testing machine. Sixty sound, freshly extracted human molars were used. Three groups (n = 20) were randomly created with different ceramic thicknesses (0.5, 0.8, and 1.2 mm), and 60 LD IPS e.max Press LT occlusal veneers were fabricated. The ceramic restorations were luted with a resin cement. The stainless-steel rotating drum of the ball mill contained 10 zirconia (Y-TZP) and 10 stainless steel spheres, in 500 mL of distilled water at 37 ± 1 °C. Crack growth in the LD restorations was evaluated under a stereomicroscope following each fatigue testing run (12 60-min runs). Progressive damage was observed as a function of cycling time. Survival was significantly influenced by the restoration thickness (p = 0.002, log-rank test), with thicker restorations exhibiting a higher survival rate. Thinner restorations (0.5 mm) showed significantly lower survival rate than 0.8- and 1.2-mm restorations (p < 0.016); no significant difference was observed between the 0.8- and 1.2-mm restorations. A threshold value of 0.8 mm may represent an acceptable compromise between fatigue resistance and tooth reduction.
Keywords: Dental ceramics; Fatigue cycling; Lithium disilicate; Occlusal veneers; Survival rate